PENGARUH HARGA MINYAK DUNIA DAN NILAI TUKAR TERHADAP RESIKO PERBANKAN SYARIAH DI INDONESIA PERIODE 2007-2018 - Multazam Mansyur Addury (Wahana Islamika: Jurnal Studi Keislaman, 2019)
Many factors can influence the risk of Islamic banking, including internal banking and external banking (macroeconomic) factors. To minimize risk, Islamic banking needs to pay attention to fluctuating macroeconomic conditions. The independent variables used in this study are world oil prices and the rupiah exchange rate. The dependent variable used in this study is credit risk as measured by NPF and liquidity risk as measured by FDR in Islamic banking. The data used in this study are secondary data which as a whole are taken from official sources in monthly form starting from January 2007 to December 2018. Data on world oil prices are obtained from OPEC Basket Price, exchange rate data obtained from Pacific Exchange Rate Service, data from NPF and FDR obtained from BI Sharia Banking Statistics (SPS-BI). The results of the study found that world oil prices had a significant effect on credit risk and liquidity risk of Islamic banking, while the exchange rate only had a significant effect on credit risk in Islamic banking.